Tetrazole Photoclick Chemistry: Reinvestigating Its Suitability as a Bioorthogonal Reaction and Potential Applications. (7th December 2015) - Li, Zhengqiu; Qian, Linghui; Li, Lin; Bernhammer, Jan C.; Huynh, Han Vinh; Lee, Jun‐Seok; Yao, Shao Q.
Abstract: The bioorthogonality of tetrazole photoclick chemistry has been reassessed. Upon photolysis of a tetrazole, the highly reactive nitrile imine formed undergoes rapid nucleophilic reaction with a variety of nucleophiles present in a biological system, along with the expected cycloaddition with alkenes. The alternative use of the tetrazole photoclick reaction was thus explored: tetrazoles were incorporated into Bodipy and Acedan dyes, providing novel photo‐crosslinkers with one‐ and two‐photon fluorescence Turn‐ON properties that may be developed into protein‐detecting biosensors. Further introduction of these photo‐activatable, fluorogenic moieties into staurosporine resulted in the corresponding probes capable of photoinduced, no‐wash imaging of endogenous kinase activities in live mammalian cells.